On the Mode of Enhanced VR Virtual Simulation Technology in the Field of Foreign Language Teaching - Haibo Zhang (Advances in Multimedia)
This paper combines virtual simulation technology to improve the traditional foreign language teaching mode. Aiming at the problems of traditional phase-shift shadow Moiré profiler, a three-step quadrature-phase demodulation technique using unknown phase shift was developed. Then, the paper compares the proposed method with the GS method using MATLAB simulation. It can be seen from the simulation and demodulation results that the two methods obtain similar results, thus proving the equivalence of the two methods.